PENTINGNYA KOMUNIKASI DALAM UPAYA MENINGKATKAN KEPUASAN TAMU DI HOTEL TUGU MALANG - Estikowati Estikowati (Universitas Merdeka Malang, 2016)
Guest satisfaction is the main core of the service which is provided in hospitality industry. Guests will feel very appreciated and respected to hotel where every employee has a good communication. Communication is very important for every department, especially in the Front Office Department. Because Front Office is the most important part when guests arrive at the hotel. Thus guests will feel comfortable to stay in the hotel. The purpose of this study was to determine the importance of good communication in maintaining and improving guest satisfaction at Hotel Tugu Malang. The research method which was used in this research were interviews and observation. The conclusion shows that the communication has a very important role to support all kinds of needs in order to avoid a miss communication.